2021
DOI: 10.1200/edbk_320463
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Cancer Care: The Example of Sarcoma—In Search of Solutions for a Global Issue

Abstract: Disparities in health care have an adverse effect on the outcome of disadvantaged patients with cancer. Patients may be at a disadvantage because of geographic isolation; insurance status; or racial, ethnic, or other factors. In this article, we examine how disparities affect the care of patients with sarcoma in the United States, Canada, and the Asia-Pacific region. Because of the rarity of sarcomas and their challenging diagnosis and complex treatment patterns, some professional or national guidelines stipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A hybrid approach to follow-up appointments between the sarcoma specialists and patient's local orthopedic/oncological specialists are also an effective method. 26 These strategies have been utilized in New Zealand more frequently over the recent years, in efforts to reduce barriers and inequities of healthcare.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A hybrid approach to follow-up appointments between the sarcoma specialists and patient's local orthopedic/oncological specialists are also an effective method. 26 These strategies have been utilized in New Zealand more frequently over the recent years, in efforts to reduce barriers and inequities of healthcare.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies will have to focus on the long‐term ramifications of the excessive delays from COVID‐19. Consequent from the pandemic, however, Telehealth/Virtual clinics have become more widely used as more efficient methods for follow‐up consultations 26,27 . They can reduce delay of follow‐up appointments and mitigate the distance and resources required for patients in rural areas as well as those of low socioeconomic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If not recognized and mitigated, these disparities can be especially profound for patients who suffer from rare diseases. Given their relative rarity, sarcomas, including EwS, present diagnostic challenges and centralized pathology review has been shown to greatly increase diagnostic accuracy in several cooperative sarcoma studies 116 – 118 . In the US, the NCCN guidelines now recommend diagnosis at an institute with access to NGS testing.…”
Section: Future Directionsmentioning
confidence: 99%
“…In the US, the NCCN guidelines now recommend diagnosis at an institute with access to NGS testing. In addition, patients with EwS receive complex multi-disciplinary care that most often requires travel to an urban center, a factor that amplifies inequities 116 . Moreover, given the unique challenges faced by AYA patients, the increased prevalence of EwS in this under-represented patient population compounds the potential for disparities in both access and outcomes 119 .…”
Section: Future Directionsmentioning
confidence: 99%